The effects of tamoxifen on learning, memory and brain tissues oxidative damage in ovariectomized and naïve female rats - Hoda Zabihi; Mahmoud Hosseini; Masoume Pourganji; Shahrbanoo Oryan; Mohammad Soukhtanloo; Saeed Niazmand (Advanced Biomedical Research, 2014)
Background: Regarding the modulatory effects of tamoxifen (TAM) on the actions of estrogen in the present study, the effects of TAM on learning, memory and brain tissues oxidative damage in ovariectomized (OVX) and naοve female rats was investigated. Materials and Methods: The animals were divided into: (1) Sham, (2) OVX, (3) Sham-tamoxifen (Sham-TAM) and (4) ovariectomized-tamoxifen (OVX-TAM). The animals of the Sham-TAM and OVX-TAM groups were treated by TAM (1 mg/kg; 4 weeks). Results : In Morris water maze, the escape latency in the OVX group was higher than in the Sham group (P < 0.01). The time latency in the animals of OVX-TAM group was lower than that of OVX group (P < 0.01); however, there were no significant differences between the Sham-TAM and Sham groups. In the probe trial, the time spent in target quadrant (Q 1 ) by the animals of OVX group was lower than that of Sham group (P < 0.01). Interestingly, the animals of OVX-TAM group spent more times in target quadrant (Q 1 ) compared with OVX group (P < 0.01). In passive avoidance test, the animals of OVX group had lower latencies to enter the dark compartment compared with the Sham group (P < 0.05). The time latency to enter the dark compartment by animals of OVX-TAM group was higher than in OVX group (P < 0.01). In OVX-TAM group, the total thiol concentration was significantly higher (P < 0.05) and malondialdehyde concentration was lower (P < 0.01) than OVX group. Conclusions: These results allow us to propose that TAM enhances learning and memory of OVX rats. The possible mechanism may be due to the protective effects against brain tissues oxidative damage.